Correction: Development of an ISFET-based enzyme assay for p-diphenol oxidase from locally isolated fungus Schizophyllum commune MF-O5. Issue 2 (11th December 2019) - Faheem, Muhammad; Khalid, Zafar Mahmood; Shabbir, Muhammad Imran; Ahmad, Bashir; Jogezai, Naqeeb Ullah; Shaukat, Uzma; Ahmad, Bilal; Ghani, Abdul; Ullah, Hanif; Shah, Muhammad Musaddiq; Shah, Waseem; Riaz, Muhammad; et al.
Abstract : Correction for 'Development of an ISFET-based enzyme assay for p -diphenol oxidase from locally isolated fungus Schizophyllum commune MF-O5' by Muhammad Faheem et al., Anal. Methods, 2019, 11, 5893–5900.